2012
DOI: 10.1128/jb.06541-11
|View full text |Cite
|
Sign up to set email alerts
|

RNA-Seq and RNA Immunoprecipitation Analyses of the Transcriptome of Streptomyces coelicolor Identify Substrates for RNase III

Abstract: RNase III is a key enzyme in the pathways of RNA degradation and processing in bacteria and has been suggested as a global regulator of antibiotic production in Streptomyces coelicolor. Using RNA-Seq, we have examined the transcriptomes of S. coelicolor M145 and an RNase III (rnc)-null mutant of that strain. RNA preparations with reduced levels of structural RNAs were prepared by subtractive hybridization prior to RNA-Seq analysis. We initially identified 7,800 transcripts of known and putative proteincoding g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 47 publications
3
37
0
Order By: Relevance
“…RNase III was also reported to cleave the mRNA for AdpA, a pleiotropic transcription factor affecting both differentiation and antibiotic production (see below) (152). Recently, RNA-Seq showed that depletion of RNase III resulted in increased levels of many transcripts, including some (SCO5608, SCO0168, and SCO0864) thought to be involved in antibiotic production (153). An alternative explanation of the effect of RNase III on antibiotic production is that RNase III is responsible for rRNA maturation, which is important for the translation of long mRNA (149,154).…”
Section: Rna Regulation Of Antibiotic Productionmentioning
confidence: 99%
“…RNase III was also reported to cleave the mRNA for AdpA, a pleiotropic transcription factor affecting both differentiation and antibiotic production (see below) (152). Recently, RNA-Seq showed that depletion of RNase III resulted in increased levels of many transcripts, including some (SCO5608, SCO0168, and SCO0864) thought to be involved in antibiotic production (153). An alternative explanation of the effect of RNase III on antibiotic production is that RNase III is responsible for rRNA maturation, which is important for the translation of long mRNA (149,154).…”
Section: Rna Regulation Of Antibiotic Productionmentioning
confidence: 99%
“…RNase III has been reasonably well studied in S. coelicolor (20)(21)(22)36), and given the extensive sequence similarity shared with RNase III in S. venezuelae, these proteins are expected to function in a similar manner. For all Streptomyces species in the StrepDB database (http://strepdb.streptomyces.org.uk/), rnc appears to be the third gene in an operon that includes genes encoding a conserved, hypothetical protein and the large ribosomal subunit protein L32 (rpmF) (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The mechanism underlying this observation is not immediately obvious, but previous RNA-seq and chromatin immunoprecipitation analyses in S. coelicolor revealed a number of membrane proteins, lipoproteins, and other secreted protein-encoding genes to be affected by the loss of RNase III (22), and it is conceivable that one or more of these contribute to increased vancomycin sensitivity or, indeed, general antibiotic sensitivity through enhanced uptake/ reduced efflux.…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…In a recent study, we have identified a number of genes whose expression is affected by the absence of RNase III. We have proposed a model in which antibiotic production in S. coelicolor is affected because of the sheer number of transcripts that are cleaved by RNase III (26). A similar situation may obtain in S. antibioticus.…”
Section: Fig 3 Growth and Actinomycin Production Of S Antibioticus Cmentioning
confidence: 99%